The Role of the Essay-Test in Acquiring Reading and Reading Comprehension Skills - Zona V. Mrkalj (University of Belgrade, Teacher Education Faculty, 2021)
The paper explores the role of the essay-test in acquiring reading and reading comprehension skills in the modern-day teaching of Serbian Language and Literature. The authors emphasize the importance of using essay-tests for obtaining the feedback on the reading comprehension level of the texts covered in regular classes, at final exams, and on the criteria-oriented knowledge tests. Two key domains are taken into consideration when designing the tasks: the narrative text, emhasizing its structure, narrative perspective, and the motivation of the characters in the function of artistic articulation; the cognitive approach to reading according to the constructive-integrative model of Walter Kintsch (Kintsch, 1988), relevant for presenting the reading construct and understanding the cognitive complexity of the tasks. The purpose of testing students using essay-tests derives from the need to assess the development of reading literacy among the students of the higher grades of elementary school.